Salary Prediction: Case Study - Nada Salaheddin Gheriyani; Dr. Jumaa Ibrahim Dbeea (African Journal of Advanced Pure and Applied Sciences, 2024)
This case study delves into the domain of salary prediction, focusing on the relationship between an individual’s years of experience and their salary. Accurate salary estimation is pivotal in career planning and talent acquisition, offering insights for both job seekers and employers. The study employs a dataset encompassing years of experience and corresponding salaries, exploring the predictive power of machine learning models, particularly linear regression. It involves data preprocessing, model training, evaluation, and interpretation. Findings provide valuable insights into salary determination and underscore the significance of years of experience. Limitations and avenues for future research are also discussed.